2010
DOI: 10.1007/s00535-010-0305-6
|View full text |Cite
|
Sign up to set email alerts
|

A simple clinical scoring system using ferritin, fasting insulin, and type IV collagen 7S for predicting steatohepatitis in nonalcoholic fatty liver disease

Abstract: NAFIC score can predict NASH in Japanese NAFLD patients with sufficient accuracy and simplicity to be considered for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(180 citation statements)
references
References 44 publications
5
173
1
1
Order By: Relevance
“…Noninvasive assessment of NASH and advanced fibrosis in NAFLD There has been intense interest in the development of biochemical markers and scoring systems for predicting NASH or fibrosis [50][51][52][53]. Circulating levels of cytokeratin-18 (CK18) fragments have been investigated most extensively as a novel biomarker for the diagnosis of NASH [50].…”
Section: Diagnosismentioning
confidence: 99%
“…Noninvasive assessment of NASH and advanced fibrosis in NAFLD There has been intense interest in the development of biochemical markers and scoring systems for predicting NASH or fibrosis [50][51][52][53]. Circulating levels of cytokeratin-18 (CK18) fragments have been investigated most extensively as a novel biomarker for the diagnosis of NASH [50].…”
Section: Diagnosismentioning
confidence: 99%
“…The score in the original NAFIC scoring system is calculated as the weighted sum of three clinical variables [Serum ferritin ≥ 200 ng/ml (female) or ≥ 300 ng/ml (male), 1 point; serum fasting insulin ≥ 10 μU/ml, 1 point; serum type IV collagen 7S ≥ 5.0 ng/ml, 2 points] (Table 1a). It has been demonstrated that the possibility of NASH is high when the NAFIC score is 2 or higher [6]. The modified NAFIC score is also a weighted sum of the scores for the three clinical variables, although the weightage given to higher fasting serum insulin levels is higher than that in the original NAFIC scoring system [Serum ferritin ≥ 200 ng/ml (female) or ≥ 300 ng/ml (male), 1 point; serum type IV collagen 7S ≥ 5.0 ng/ml, 2 points; serum fasting insulin 10-15 μU/ml, 1 point and ≥ 15 μU/ml, 2 points] (Table 1b).…”
Section: Clinical and Laboratory Evaluationmentioning
confidence: 99%
“…Ferritin (ng/ml) <200 (female) or <300 (male) 0 ≥200 (female) or ≥300 (male) 1 Type IV collagen 7S (ng/ml) <5 0 ≥5 2 Table 1a: The criteria in the original NAFIC scoring system [6,10].…”
Section: ≥10mentioning
confidence: 99%
See 2 more Smart Citations